EFEKTIVITAS MODEL MIND MAP DALAM MENINGKATKAN KEMAMPUAN MENULIS ARTIKEL OLEH SISWA KELAS XI SMA SWASTA RAKYAT SEI GELUGUR TAHUN PEMBELAJARAN 2012/2013 - Monto Kannegi Br. Ginting (Basastra, 2013)
This research was conducted to describe the effectiveness of the method of mind map to write article. Experience and interviews indicate that many students who have difficulty writing article with precise slection of learning methods used by teachers. The selection and use of appropriate methods are needed to improve students' skills in writing article. This research was conducted to address the student's difficulties in writing article, by using the method of mind map. After doing reseased. This is evidenced by an increase in average value of experimental class students. Besides hypothesis testing also proved that the alternative hypothesis is accepted. Thus, teachers are advised to use mind map method so that students learn more actively and comfortably fits obtained imagination of mind, especially in writing article. Keywords: writing article, mind map method